Lower resting state heart rate variability relates to high pain catastrophizing in patients with chronic whiplash-associated disorders and healthy controls - Koenig, Julian (Pain practice, 2016)
Vagally mediated heart rate variability (vmHRV) is widely respected as a psychophysiological measure of emotion regulation capacity and serves as a readily available index of executive brain areas that exert an inhibitory influence on subcortical structures. Pain catastrophizing (PC) is conceptualized as the tendency to misinterpret and exaggerate pain-related situations that may be threatening. Chronic pain patients show lower vmHRV and higher PC. Previously, no study has investigated the association of PC and vmHRV. We examined the association of PC and vmHRV in a sample of patients with chronic whiplash-associated disorders (WAD, n = 30) and healthy controls (n = 31). Patients with WAD showed lower vmHRV, indexed by high-frequency HRV (effect size, Cohen's d = 0.442), and greater PC (d = 0.815). Zero-order and partial correlations controlling for age and sex revealed that vmHRV and PC are inversely related. The results provide evidence for a psychophysiological mechanism underlying PC, in particular in chronic pain patients.
Gesehen am 29.04.2020
First published: 28 November 2015